2019
DOI: 10.1002/acr2.11095
|View full text |Cite
|
Sign up to set email alerts
|

Internalized and Anticipated Stigmatization in Patients With Gout

Abstract: Objective. To investigate the relationship between stigma perception and demographic, clinical, and psychosocial variables.Methods. A sample of 50 patients with gout and prescribed urate-lowering medication (84% were males, mean serum urate 0.34 mmol/l) completed questionnaires on internalized and anticipated stigma, demographics, clinical gout-related variables, and psychosocial variables (illness perceptions, illness-related disability, illness-related body satisfaction, intentional nonadherence). Serum urat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“… 32 A cross-sectional study revealed that 26.0% of the patients experienced internalized stigma. 33 Thus, healthcare providers should consider the mental health of patients and provide strategies to help them overcome negative emotions.…”
Section: Discussionmentioning
confidence: 99%
“… 32 A cross-sectional study revealed that 26.0% of the patients experienced internalized stigma. 33 Thus, healthcare providers should consider the mental health of patients and provide strategies to help them overcome negative emotions.…”
Section: Discussionmentioning
confidence: 99%
“… 76 The persistent contemporary cultural narratives about the role of dietary and alcohol excess as the cause of disease lead to excessive focus on dietary solutions as the primary approach to manage gout and can create stigma and embarrassment about the condition. 152 , 153 …”
Section: How Can We Manage Gout Better?mentioning
confidence: 99%
“…76 The persistent contemporary cultural narratives about the role of dietary and alcohol excess as the cause of disease lead to excessive focus on dietary solutions as the primary approach to manage gout and can create stigma and embarrassment about the condition. 152,153 Health systems and health care professionals play an important role in enabling adherence and improving gout care. Low-cost pharmacy interventions have shown modest improvements.…”
Section: Renal Diseasementioning
confidence: 99%
“…Consistent with depictions of the illness in historical art and literature [ 5 ], gout is widely viewed in contemporary society as a humorous, self-inflicted condition caused by dietary excess [ 6 ]. These views can contribute to stigma and embarrassment about gout [ 7 ], and influence patients’ lay beliefs or illness perceptions [ 8 ]. Inaccurate beliefs about gout can also lead to ineffective management strategies, and contribute to worse outcomes [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%